Travels of Ali Bey, in Morocco, Tripoli, Cyprus, Egypt, Arabia, Syria, and Turkey between the years 1803 and 1807, written by himself and illustrated by maps and numerous plates. - Badia y Leblich, Domingo, 1767-1818. (London)
2. c. (ix, [1], 373 s., y. xlv-lxxiii resim, plan (kimi katlı), [2] katlı sayfa harita)